The technique of using Description Logics in the process of constructing a composite service at the functional level - Zakharova, O.V. (PROBLEMS IN PROGRAMMING, 2018)
Automated composition is one of the most difficult web-services tasks. It has two purposes: first is to satisfy complex client’s requirements, second is to reduce a complexity of developing web-service to satisfy complex application system. Created theoretical apparatus is the basis for developing the algorithms of automated solving a semantical web-services composition task. Proposed approaches are based on using description logics. It is effective and powerful tool due to its mechanisms of judgments and the possibilities of logical inference and giving semantic meaning to descriptions.Problems in programming 2018; 1: 77-91